2021
DOI: 10.1053/j.semtcvs.2020.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Regurgitation Index Ratio Is a Strong Predictor of 1-Year Mortality After Transcatheter Aortic Valve Implantation Using Self-Expanding Devices

Abstract: Index ratio is a strong predictor of one-year mortality after transcatheter aortic valve implantation using self-expanding devices,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Previously, we showed that ARI ratio < 0.6 is the strongest haemodynamic predictor of 1-year mortality after TAVR. 36 In the present study, interestingly ARI ratio was least predictive for the occurrence of CMR-RF > 20%. Indeed, for clinical outcome not only the post-TAVR occurrence of PVR is important but also the pre-TAVR haemodynamic circumstances like diastolic dysfunction and pre-existing aortic regurgitation.…”
Section: Discussionsupporting
confidence: 41%
“…Previously, we showed that ARI ratio < 0.6 is the strongest haemodynamic predictor of 1-year mortality after TAVR. 36 In the present study, interestingly ARI ratio was least predictive for the occurrence of CMR-RF > 20%. Indeed, for clinical outcome not only the post-TAVR occurrence of PVR is important but also the pre-TAVR haemodynamic circumstances like diastolic dysfunction and pre-existing aortic regurgitation.…”
Section: Discussionsupporting
confidence: 41%
“…Several previous studies have assessed the impact of hemodynamic indices on prognosis after TAVI. With the majority of studies showing a significant association with survival [14,[22][23][24][25], two investigations from the same centre recently suggested contradictory findings regarding short-and long-term outcomes on mortality [26,27]. However, to our knowledge, only one study showed the impact of a time-integrated aortic regurgitation index (TIARI) on PVL requiring PD [9].…”
Section: Discussionmentioning
confidence: 99%
“…24 In contrast, this is almost entirely absent in conventional valve implantation as our study and other papers show. 17 Paravalvular leakage increases the risk of premature death as TAVI data indicate, 25 and it is a risk for the development of an endocarditis, as well as anemia, owing to chronic hemolysis. 26 It can be speculated that it is too early for these problems to be revealed in studies dealing with low-risk patients for being elusive in the early period.…”
Section: Discussionmentioning
confidence: 99%